2021
DOI: 10.1093/hmg/ddab147
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the impact of alcohol consumption on the genetic contribution to mean corpuscular volume

Abstract: The relationship between the genetic loci that influence mean corpuscular volume (MCV) and those associated with excess alcohol drinking are unknown. We used white British participants from the UK Biobank (n = 362 595) to assess the association between alcohol consumption and MCV, and whether this was modulated by genetic factors. Multivariable regression was applied to identify predictors of MCV. GWAS, with and without stratification for alcohol consumption, determined how genetic variants influence MCV. SNPs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
0
1
1
Order By: Relevance
“…We found blood cell vQTLs tagged genes related to diet. Previous GWAS of diet identified loci related to blood lipids 38 and glycated hemoglobin 39 but not to blood cell traits analysed here; however, others have reported that alcohol intake increases mean corpuscular volume independent of the genetic contribution to the level of mean corpuscular volume 40 . In our study, alcohol consumption-related loci significantly overlapped with vQTLs for platelet count, the function of which can be significantly affected by alcohol drinking 41 .…”
Section: Discussioncontrasting
confidence: 61%
“…We found blood cell vQTLs tagged genes related to diet. Previous GWAS of diet identified loci related to blood lipids 38 and glycated hemoglobin 39 but not to blood cell traits analysed here; however, others have reported that alcohol intake increases mean corpuscular volume independent of the genetic contribution to the level of mean corpuscular volume 40 . In our study, alcohol consumption-related loci significantly overlapped with vQTLs for platelet count, the function of which can be significantly affected by alcohol drinking 41 .…”
Section: Discussioncontrasting
confidence: 61%
“…Overall, four genes ( SCAMP2, SCAMP5, MPI, and FAM219B ) were identified by all four methods, and six of the 165 discovered genes ( FBXO28 , NEIL2 , HAUS4 , IGDCC4 , RP11- 298I3.5 , RP11-298I3.5 ) were not within 1Mb of SNPs identified by prior GWAS of coffee or caffeine traits ( Supplementary Table 11 ; Figure 1B ; Table 2 ). These novel genes have been associated with substance use (e.g., HAUS4 and smoking initiation 73 ), educational outcomes (e.g., HAUS4 and educational attainment 90 ), and biomarkers (e.g., FBXO28 and mean platelet volume 91 ; IGDCC4 and mean corpuscular volume 92 ).…”
Section: Resultsmentioning
confidence: 99%